The impact of the drought on Spanish water policy from 1850 to 1975. Some facts about the Barrios de Luna reservoir (León) - Junquera Rubio, Carlos (Observatorio Medioambiental, 2018)
The word "drought" has been common in the history of Spain. In the middle of the 19th century, the opinion began to circulate that water should be property of the State and should be used to irrigate large areas that were waiting for this resource and that would not be lost in the sea without fertilizing the fields before. The projects to build dams come precisely from this need. Initiating this task needed a new legal regulation. In 1889 the first Civil Code was promulgated and the Water Law of 1879 could be implemented. Between the years 2015 and 2017, the rains have been absent from Spanish landscapes and dams, so that of 50 years ago or more are disappearing. The impact of drought is present in all the basins; moreover, they are almost without water resources. This situation has generated social alarm and, if persisted, will jump to politics. This essay addresses drought and lack of water as a problema in the last century and a half of the history of Spain, since 1850.